Pengaruh Efikasi Diri Dan Pendidikan Kewirausahaan Terhadap Minat Wirausaha Mahasiswa Pendidikan Ekonomi Universitas Panca Sakti - Putri, Eka (Universitas Indraprasta PGRI, 2021)
This study aims to determine the effect of self-efficacy and entrepreneurship education on interest in entrepreneurship. The research was conducted on students of Economics Education Class of 2019 who have completed the Entrepreneurship Education course. This research uses the associative quantitative method with a series of instrument tests and classical assumption tests. The sample in this study were 52 people. The sampling technique was done randomly. The type of data used is primary data, then the data is analyzed using partial t-test and F-test. Based on the results of data analysis, the results of the study can be concluded as follows: (1). Self-efficacy of students of the economic education study program at Panca Sakti University in Bekasi does not significantly affect the interest in entrepreneurship. (2). Entrepreneurship education for students of the Economic Education study program at the Panca Sakti University in Bekasi has a significant effect on interest in entrepreneurship. (3). Self-efficacy and entrepreneurship education together have an effect on the entrepreneurial interest of students in the economic education study program at Panca Sakti University BekasiÂ